Re-innovation from failure, institutional environmental differences, and firm performance: Evidence from China - Zhuang Xiong; Pengju Wang; Yu Zhao (Amfiteatru Economic Journal, 2020)
Due to an anti-failure bias, theoretical and practical studies have not focused much on the problem of innovation failure. The literature does not include studies on how the effect of re-innovation input on firm performance can still be explained by existing theories, especially in the case of previous innovation failures. To explore the intrinsic relationship between the re-innovation from failure and firm performance, as well as the influencing mechanism of the institutional environment differences on a firm's re-innovation activities, using the data of the Listed Companies in China's pharmaceutical manufacturing industry from 2008 to 2014 and a multiple regression model, the relationships between the re-innovation from failure, institutional environment differences, and firm performance were analyzed from 3 aspects: government intervention, financial development, and legal environment. The results show that the re-innovation input from failure has a significant positive impact on firm performance. The level of government intervention and the level of financial development play significant negative and positive moderating roles in the relationship between the re-innovation input and firm performance, respectively, and the above-mentioned effects are more prominent in eastern China. Moreover, with the improvement of the marketization of the financial industry, the beneficial effect of the re-innovation input from failure on firm performance in state-owned firms will be further strengthened. However, the moderating effect of the legal environment is not obvious.
Keywords: M13; O32; O33; O38; 330; re-innovation from failure; institutional environment; firm performance; moderating effect